Assessing Readiness to pay for HIV Services in Developing Asian Countries: A Systematic Review of Willingness to Pay Studies - Sihotang, Erik Parulian; Pujiyanto; Bachtiar, Adang; Candi, Cicilya (UIMA Press, 2026)
Developing Asian countries continue to face financial challenges in ensuring equitable access to HIV services. Despite numerous initiatives to expand coverage and improve treatment outcomes, affordability remains a major barrier. This systematic review, conducted using PRISMA methodology, analyzes willingness to pay (WTP) and readiness to pay (RTP) for HIV-related services, based on 14 studies selected from an initial pool of 6,773 articles identified through three major databases (PubMed, Scopus, and ProQuest) covering peer reviewed publications between 2015 and 2025. Focusing on at-risk populations in India, China, Vietnam, Iran, and the Philippines, the review examines services such as HIV self-testing kits, antiretroviral therapy (ART), pre-exposure prophylaxis (PrEP), and viral load monitoring. Findings reveal significant variation in WTP/RTP influenced by education, income, HIV awareness, stigma, and privacy concerns. For instance, 69% of respondents in India were willing to pay for self-testing kits, compared to only 6.8% of MSM in China willing to pay market rates for PrEP. RTP extends beyond financial capacity to include behavioral, social, and cultural readiness, which plays a critical role in service uptake. The review concludes that WTP/RTP alone is insufficient for achieving universal HIV care. It recommends adaptive policies such as hybrid financing models, targeted health education, and government subsidies to ensure sustainable and inclusive HIV service delivery.